If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12(-5 + -1b) = 1(b + 16) (-5 * -12 + -1b * -12) = 1(b + 16) (60 + 12b) = 1(b + 16) Reorder the terms: 60 + 12b = 1(16 + b) 60 + 12b = (16 * 1 + b * 1) 60 + 12b = (16 + 1b) Solving 60 + 12b = 16 + 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 60 + 12b + -1b = 16 + 1b + -1b Combine like terms: 12b + -1b = 11b 60 + 11b = 16 + 1b + -1b Combine like terms: 1b + -1b = 0 60 + 11b = 16 + 0 60 + 11b = 16 Add '-60' to each side of the equation. 60 + -60 + 11b = 16 + -60 Combine like terms: 60 + -60 = 0 0 + 11b = 16 + -60 11b = 16 + -60 Combine like terms: 16 + -60 = -44 11b = -44 Divide each side by '11'. b = -4 Simplifying b = -4
| ln(6x)+1=1 | | t^4+6t^2+9=t^2+3+12 | | 3+6x=5x+1 | | 11x+8=13x+4 | | ln(6x)+ln(5)=1 | | ln(6x)-ln(13-3x)=1 | | -8+6x=1+3x | | 0.3x-0.1=0.5-0.4(9-2x) | | 2-3(y-2)=2(y+4)+5 | | r^2-4r=3r+30 | | x=5-2x | | 0=0.75x+3 | | 5x+4=8y+4 | | -89=n+7(n-7) | | (x)(x)-34=(x+2)(x-5) | | -31-4x=-5-5(2+5x) | | t^4+9=t^2+3+12 | | -5x+6(4x+17)=197 | | x-34=(x+2)(x-5) | | 5(-9-3d)= | | 1.5x^2+0.5x=3 | | -144=-4(1-7m) | | 2x+4(3x+17)=152 | | 3sinx+y^3=5x^2 | | -34=(x+2)(x-5) | | 9x=8x+32 | | (P+5)+2= | | 12x-12=4x+28 | | -140=4x-2(-4x+10) | | 5x-15+2=-13+5x | | 3(x+1)1+2x=2(2x+2)+x | | 6y+4x=8 |